The effect of contextual interference on transfer in motor learning - a systematic review and meta-analysis - Czyż, Stanisław H.; Wójcik, Aleksandra M.; Solarská, Petra (Frontiers in Psychology, 2024)
Since the initial study on contextual interference (CI) in 1966, research has explored how practice schedules impact retention and transfer. Apart from support from scientists and practitioners, the CI effect has also faced skepticism. Therefore, we aimed to review the existing literature on the CI effect and determine how it affects transfer in laboratory and applied settings and in different age groups.We found 1287 articles in the following databases: Scopus, EBSCO, Web of Science, PsycINFO, ScienceDirect, supplemented by the Google Scholar search engine and manual search. Of 300 fully screened articles, 42 studies were included in the systematic review and 34 in the quantitative analysis (meta-analysis).The overall CI effect on transfer in motor learning was medium (SMD=0.55), favoring random practice. Random practice was favored in the laboratory and applied settings.However, in laboratory studies, the medium effect size was statistically significant (SMD=0.75), whereas, in applied studies, the effect size was small and statistically nonsignificant (SMD=0.34). Age group analysis turned out to be significant only in adults and older adults. In both, the random practice was favored. In adults, the effect was medium (SMD=0.54), whereas in older adults was large (SMD=1.28). In young participants, the effect size was negligible (SMD=0.12).